Performance of Joint Antenna Selection Schemes in Energy Harvesting Cooperative Networks - Çağiran, Harun; Kucur, Oğuz (Institute of Electrical and Electronics Engineers Inc., 2022)
In this work, we investigate performance of dual-hop half-duplex, multiple-input multiple-output network with energy harvesting (EH). A direct path exists between source and destination and analyses are done for flat Nakagami-m channels. The transmission is accomplished in two time slots. In the first time slot, relay node makes energy harvesting by power splitting EH protocol. In the second time slot, the relay node transmits the signal with amplify-and-forward method by using the harvested energy. Two different schemes based on joint transmit and receive antenna selection are used in the direct and relaying paths. At the destination, selection combining is applied between relaying and direct paths. Outage probability (OP) and symbol error rate of the network are analyzed. In addition, asymptotic OP expression is derived for diversity order. Theoretical derivations are verified by Monte Carlo simulations. © 2023 Elsevier B.V., All rights reserved.
13th International Conference on Computing Communication and Networking Technologies, ICCCNT 2022 -- Kharagpur -- 185582
Keywords: Cooperative Communication; Energy Harvesting; Joint Antenna Selection